The Contribution of Murabahah Financing in Improving the Financial Performance of Islamic Banks in Indonesia: An Empirical Perspective - Muflihan, Muflihan; Najwa , Najwa Shifa Qursya (Alhamdulillah : Jurnal Agama Islam, 2023)
The purpose of this study is to analyze the impact of murabahah financing on the financial performance of Islamic banks in Indonesia. Using secondary data from Islamic bank financial reports for the period 2018-2022, this study applies multiple linear regression analysis to test the relationship between murabahah financing and financial performance variables such as profitability, operational efficiency, and asset growth. The results of the analysis show that murabahah financing has a positive and significant effect on profitability and asset growth, while its effect on operational efficiency is lower. Murabahah financing has proven effective in improving the financial performance of Islamic banks, both in terms of stable income and cost management. This study provides guidance for Islamic banks to further develop murabahah financing strategies by considering risk management and diversification of financing products.